Acercamiento a la transitividad en el náhuatl de Tlaxcala - Fernández Jiménez, Alfredo (Wydawnictwo Naukowe Uniwersytetu im. Adama Mickiewicza w Poznaniu, 2004)
In this paper I explore transitivization in Náhuatl, a language spoken in Tlaxcala, México. I follow Hopper and Thompson's proposition of graduate transitivity from a typological point of view. I analyse the grades of transitivity of perfective/imperfective clauses. From the inherent lexic aspect (Foley and Van Valin, 1984) I will analyze the opposition of generic vs. defined referent in a clause.
Approach to the Transitivity in Nahuatl of Tlaxcala